Experimental Investigation Of Different Rules Size Of Fuzzy Logic Controller For Vector Control Of Induction Motor Drives - Talib, Md Hairul Nizam; Yahya Farah, Nabil Salem; Ibrahim, Zulkifilie; Rasin, Zulhani; Rizman, Z. I. (J Fundam Appl Sci., 2018)
There is lack of performance comparison investigation between 49,25 and 9 rules size speed controller of Induction Motor (IM) drives of the rules size toward the motor performance. Furthermore, no study was conducted based on the computation burden time affects by the rules experimentally fuzzy rules sizes in terms of performance based on simulations and experimental analysis as well as the execution time.MATLAB/SIMULINK and dSPACE DSl104 controller platform are used for the analysis. Variation in performance with the shape and number of membership functions.Based on the experimental results,it can be concluded that,higher number of rules increase the Computational Time (CT), hence bigger sampling time is required which will There is lack of performance comparison investigation between 49,25 and 9 rules size speed controller of Induction Motor (IM) drives.Thus,it is difficult to understand the effect of the rules size toward the motor performance.Furthermore, o study was conducted based on the computation burden time affects by the rules experimentally.This paper compares the fuzzy rules sizes in terms of performance based on simulations and experimental analysis as well as the execution time. MATLAB/SIMULINK and dSPACE DSl104 controller platform are used for the analysis.Variation in performance with different rule size may occur due to the shape and number of membership functions.Based on the experimental results,it can be concluded that,higher number of rules increase the Computational Time (CT),hence bigger sampling time is required which will affect the performance.There is lack of performance comparison investigation between 49,25 and 9 rules sizefor the. Thus, it is difficult to understand the effect of the rules size toward the motor performance.Furthermore,no study was conducted based.This paper compares the fuzzy rules sizes in terms of performance based on simulations and experimental analysis as well as the execution time. MATLAB/SIMULINK and dSPACE DSl104 controller platform different rule size may occur due to the shape and number of membership functions.Based on the experimental results, it can be concluded that, higher number of rules increase the Computational Time (CT),hence bigger computational time (CT).